IMPLEMENTASI HUKUM PENGGUNAAN HAK CIPTA SEBAGAI OBJEK JAMINAN FIDUSIA DALAM PERJANJIAN KREDIT BANK - Sintia Evitaveren Sidauruk (Cahaya Ilmu Bangsa, 2025)
This Thesis is conducted to examine the validity of copyright as an object of fiduciary collateral in bank credit agreements in Indonesia, as well as the challenges in the application and execution of copyright as collateral. This study is a normative legal study of data collection carried out using a statutory approach and also a conceptual approach. From the results of the study, it can be concluded that although Article 16 paragraph (3) of Law Number 28 of 2014 concerning Copyright recognizes copyright as an object of fiduciary collateral, in the implementation of copyright in the field there are still several obstacles such as the lack of specific regulations regarding the clarity of the application of the contents of Article 16 paragraph (3). In addition, related to execution, Copyright cannot be executed physically. However, the economic value of Copyright can be executed through a public auction or private sale according to the Copyright transfer procedure in Article 16 paragraph (2) of Law Number 28 of 2014 concerning Copyright.